A Review on Thermal Desorption Treatment for Soil Contamination - Risky Ayu Kristanti; Wilawan Khanitchaidecha; Gaurav Taludar; Peter Karácsony; Linh Thi Thuy Cao; Tse-Wei Chen; Noura M. Darwish; Bandar M. AlMunqedhi (Tropical Aquatic and Soil Pollution, 2022)
Soil contamination is a major issue that must be prioritized, as food safety is mostly determined by soil quality. Soil quality has deteriorated significantly across the world with the continued expansion of industrial growth, urbanization, and agricultural activities. Soil contamination has become a growing issue and a barrier that must be addressed if we are concerned about re-establishing a healthy ecosystem. The activity is mostly driven by human activities, which include the use of pesticides, chlorinated organic pollutants, herbicides, inorganic fertilizers, industrial pollution, solid waste, and urban activities. While many methods have been developed to remediate significant pollutants generated by these activities, their degree of application may be constrained or inappropriate for a specific location. Parameters such as treatment duration, safety, and efficacy of soil/pollutant treatment all play a part in selecting the best appropriate technique. These technologies have been classified into three broad categories: physical, chemical, and bioremediation. This review shows and talks about thermal desorption (TD), which is a common way to clean up polluted soil.